Análise da outorga de direito de uso dos recursos hídricos no estado do Ceará - Costa, José Nilton de Abreu (2011)
This study is an analysis of the system for granting rights of usage of water resources, currently developed in the State of Ceará. This analysis was based on data relating to the grant, provided by the managing agencies (SRH and COGERH). In reviewing the literature, the concept of grant was analysed in the legal and technical contexts and have discussed the laws pertaining to the topic at the state and federal scope. The steps in the process of requesting and obtaining the grant, the legal aspects related to the theme and the role of grants as a tool for management of water resources contained in PNRH are evaluated by the flowchart of SRH. Information on quantity and flow of the grants awarded from October 1996 to October 2010, in each watershed of Ceará were presented by using graphics. It was evidenced the importance of granting the right to use water as a tool quality control of that resource. Finally, some recommendations were presented for a possible greater efficiency in implementing the grant and in ensuring the attendance to the real needs of the population.